Analisis Pengaruh Pemasaran Hubungan Pelanggan, Nilai Pelanggan Terhadap Kepuasan Pelanggan Dan Implikasinya Terhadap Loyalitas Pelanggan - Tri Ningsih (Majalah Bisnis Dan IPTEK, 2016)
This study was conducted to determine how customer relationship marketing, and customer value that is applied at one salon existing Muslim city of Bandung, and its influence on customer satisfaction in the Muslim salon as well as to see how the implications for consumer loyalty. The independent variables were investigated alleged to have a strong influence on customer loyalty compared with other variables that are not included in this study. The method used in this research is survey method. While the population of the study where consumers have an infinite amount, the researchers took samples of the iteration technique, where the technique is used when the population of the infinite. To find out how the influence of the independent variables in this study on customer loyalty used path analysis with the help of LISREL software. The results of data processing found that the independent variable is customer relationship marketing and customer value effect simultaneously with a total effect of 0,532 or by 53.2%. While partially, customer relationship marketing has a significant influence against the influence of customer satisfaction with 26.3%, variable customer value has significant impact on customer satisfaction. As much influence 26.9% and customer satisfaction has significant impact on customer loyalty with great effect of 73.1%.